Variants of NESTOR injection remote control - Akchurin, Yu.I.; Ivakhnenko, M.V.; Orlova, E.I. (Вопросы атомной науки и техники, 2014)
The two variants of remote control linac-60 for injection of the electron beam in the storage-ring ''NESTOR'' is described. First variant of the autonomous remote control for linac design from the decoder 155ID3. In the second variant use ADAM–4051 as encoder, while the decoders are the controllers ADAM-5051E, using for auto-loking and plase control linac. The controllers help automation process diagnostics of this accelerator during its malfunction.